Different impacts of similar crises? The financial and COVID-19 crisis in border and non-border regions - Hippe, Stefan (European Planning Studies, 2024)
The last two decades have seen an increase in the number and intensity of shocks and crises. The financial crisis of 2008/2009 and the COVID-19 crisis of 2020/2021 have led to economic recessions. During the COVID-19 crisis, national borders and the impact of crises in border regions were often the subject of political debate and media coverage. Border-regional resilience has only been discussed in the academic discourse for the last few years. This article uses a diverse set of socio-economic indicators to examine the (border)–regional resilience of German regions in the wake of the financial crisis and the COVID-19 crisis. A distinction is made between border and non-border regions, urban and rural regions, and regions in the old and new German federal states. The results show, first, that the COVID-19 crisis had a stronger socio-economic impact than the financial crisis. Second, border regions tended to be more affected by the financial crisis than non-border regions. Surprisingly, this was not the case for the border-specific COVID-19 crisis. Moreover, the study shows that it is not so much the border location that determines regional resilience, but rather the socio-economic level, the degree of urbanization and the associated embeddedness in global networks.<br
Keywords: border studies; border-regional resilience; COVID-19 crisis; financial crisis; resilience